PD-1/PD-L1 combined with LAG3 is associated with clinical activity of immune checkpoint inhibitors in metastatic primary pulmonary lymphoepithelioma-like carcinoma - Zhong, Yu-Min; Yin, Kai; Chen, Yu; Xie, Zhi; Lv, Zhi-Yi; Yang, Jin-Ji; Yang, Xue-Ning; Zhou, Qing; Wang, Bin-Chao; Zhong, Wen-Zhao; Gao, Ling-Ling; Zhou, Wen-Bin; et al. (Frontiers in Immunology, 2022)
Primary pulmonary lymphoepithelioma-like carcinoma (PLELC) is an Epstein-Barr virus (EBV)-related and rare subtype of non-small cell lung cancer (NSCLC). Immune checkpoint inhibitor (ICI) showed enduring response in advanced NSCLC. However, the effect of ICI and predictive biomarkers in PLELC remains poorly understood. We retrospectively analyzed 48 metastatic PLELC patients treated with ICI. Pretreated paraffin-embedded specimens (n=19) were stained for PD-1, PD-L1, LAG3, TIM3, CD3, CD4, CD8, CD68, FOXP3, and CK by multiple immunohistochemistry (mIHC). Next-generation sequencing was performed in 33 PLELC. For patients treated with ICI monotherapy (n=30), the objective response rate (ORR), disease control rate (DCR), median progression free survival (mPFS) and overall survival (mOS) were 13.3%, 80.0%, 7.7 months and 24.9 months, respectively. Patients with PD-L1≥1% had a longer PFS (8.4 vs. 2.1 months, p=0.015) than those with PD-L1<1%. For patients treated with ICI combination therapy (n=18), ORR, DCR, mPFS and mOS were 27.8%, 100.0%, 10.1 months and 19.7 months, respectively. Patients with PD-L1≥1% presented a significantly superior OS than those with PD-L1<1% (NA versus 11.7 months, p=0.001). In the 19 mIHC patients, cases with high PD-1/PD-L1 and high LAG3 expression showed a longer PFS (19.0 vs. 3.9 months, p=0.003) than others. ICI showed a promising efficacy in metastatic PLELC. PD-L1 might be both predictive of ICI treatment and prognostic for survival in PLELC. PD-1/PD-L1 combined with LAG3 could be a significantly predictive marker for ICI treatment in PLELC. Larger and prospective trials are warranted to validate both ICI activity and predictive biomarkers in PLELC.